Spatial risk assessment of population density and land use: Challenges and solutions for sustainable urban development - Ibnu Hafizh Syam (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The growth of major cities is directly related to the increasing population and rising density. The Special Capital Region (DKI) of Jakarta is the most densely populated, with 15,292 people/km² and a population growth rate of 1.11% per year. Land use in Kapuk Village consists of five main types, including residential, religious, socio-cultural, commercial, and other uses. The dominant land use in Kapuk Village is for residential purposes, covering an area of 2.566 km². Kapuk Village is the most densely populated village in Indonesia. Building density is related to the number of residents living in the area. Kapuk Village has the highest population, with a total of 174,349 people and a population density of 34,014 people/km². Vertical housing is a spatial planning concept where housing is built upward and can address land limitations in urban areas. According to data from the Jakarta Provincial Government, slum settlements in Kapuk Village cover an area of 2,594 km² or approximately 50.57% of the total area of Kapuk Village. Methods: This study employs a qualitative approach with descriptive analysis, integrating literature reviews and secondary data from the Central Statistics Agency and Jakarta Provincial Government. Spatial analysis techniques are applied using land use maps, building density maps, and slum settlement distributions to examine the correlation between population density and urban development patterns. Findings: The study reveals that residential land dominates Kapuk Village, covering 2,566 km², with slum areas comprising 50.57% of the total land. High building density contributes to limited open spaces and increased surface temperatures, affecting urban livability. The demand for social services, education, and healthcare surpasses available facilities, worsening urban disparities. The study also identifies the potential of vertical housing as a sustainable solution to accommodate the growing population. Conclusion: The research highlights the urgent need for strategic urban planning to address land use inefficiencies and mitigate the negative impacts of overpopulation. Vertical housing, combined with improved infrastructure and social services, can enhance urban resilience. Novelty/Originality of this article: This study provides a comprehensive spatial analysis of population density and land use in Kapuk Village, highlighting the direct impact on urban sustainability. It offers a novel perspective on integrating land use planning with social and environmental factors to promote better urban management strategies.